The effect of inlet conditions on the flow and heat transfer in a multiple rotating cavity with axial throughflow - Long,CA; Childs,PRN (2006)
This paper discusses experimental results from two different build configurations of a heated multiple rotating cavity test rig. Measurements of heat transfer from the discs and tangential velocities are presented.The test rig is a 70 % full scale version of a high pressure compressor stack of an axial gas turbine engine. Of particular interest are the internal cylindrical cavities formed by adjacent discs and the interaction of these with a central axial throughflow of cooling air. Tests were carried out for a range of non-dimensional parameters representative of high pressure compressor internal air system flows (Reφ up to 5 x 106 and Rez up to 2 x 105). Two different builds have been tested. The most significant difference between these two build configurations is the size of the annular gap between the (non-rotating) drive shaft and the bores of the discs.The heat transfer data were obtained from thermocouple measurements of surface temperature and a conduction solution method. The velocity measurements were made using a two component, LDA system. The heat transfer results from the discs show differences between the two builds. This is attributed to the wider annular gap allowing more of the throughflow to penetrate into the cavity. There are also significant differences between the radial distributions of tangential velocity in the two builds of the test rig. For the narrow annular gap, there is an increase of non-dimensional tangential velocity Vφ / Ωr with radial location to solid body rotation Vφ / Ωr = 1. For the wider annular gap, the non-dimensional velocities show a decrease with radial location to solid body rotation.